FORMATION OF MODERN MEMORIAL SPACES AS AN ENVIRONMENT OF MULTISENSORY PERCEPTION OF MEMORY - Lysuchevska, Maryna; Kosyk, Oksana (Theory and practice of design, 2025)
Purpose. The purpose of the article is to study the multisensory perception of memory in the context of the formation of memorial spaces and to determine the influence of the combination of sensory, cognitive, and emotional perception channels on collective consciousness. The focus is on analyzing the role of such spaces in preserving historical memory, maintaining cultural continuity, and developing social reflection. Methodology. The research applies a comprehensive interdisciplinary approach that combines elements of cultural, psychological, architectural, and socio-communicative analysis. Methods of comparative analysis of world memorial sites, a structural-functional approach to studying spatial organization and visual-sensory characteristics, as well as content analysis of materials devoted to the design of modern memorial environments, were used. Results. The article substantiates that multisensory perception of memory ensures deeper emotional engagement of visitors to memorial spaces, stimulates empathy, and promotes the formation of stable associative links between the past and the present. It was found that architectural form, sound and light effects, tactile and spatial solutions create a synergistic effect that activates mechanisms of collective remembering. Analyzed examples of memorial objects in different countries demonstrate the diversity of artistic and technological approaches to representing historical memory and its integration into the urban environment. The significance of memorial spaces as tools of civic education, moral development, and cultural dialogue is emphasized. Scientific novelty. For the first time, multisensory perception is considered a key factor in the effectiveness of a memorial space that combines aesthetic, psychological, and communicative dimensions of influence on visitors. The potential of integrating sensory technologies into the design process of modern memorial objects to enhance emotional and cognitive impact is revealed. The author proposes an interpretation of the memorial space as a dynamic environment of collective experience capable of influencing social narratives and shaping new models of memory. Practical relevance. The obtained results can be used in developing architectural and artistic concepts of memorial complexes, designing public spaces, and in museum and educational practice. The conclusions of the study have applied importance for urban studies, cultural policy, and heritage management aimed at preserving historical memory and strengthening the sociocultural unity of society.